Sociodemographic factors and STIs associated with Chlamydia trachomatis and Neisseria gonorrhoeae infections in Zambian female sex workers and single mothers. (March 2020) - Connolly, Sarah; Wall, Kristin M; Parker, Rachel; Kilembe, William; Inambao, Mubiana; Visoiu, Ana-Maria; Sharkey, Tyronza; Hunter, Eric; Allen, Susan
Sexually transmitted infections (STIs) in women caused by Chlamydia trachomatis (CT) and/or Neisseria gonorrhoeae (NG) are epidemiologically distinct. In this study, associations with sociodemographic and clinical risk factors are explored separately for CT and NG. Multivariate logistic regression (MLR) models quantify associations between potential CT and/or NG risk factors within a cross-sectional study of high-risk women in two Zambian cities, Lusaka and Ndola. CT was associated with living in Lusaka, younger age, and literacy. Long-acting reversible contraception (LARC) was predictive of CT in Ndola, but protective in Lusaka. In Lusaka only, CT was associated with lower education and reported unprotected sex. NG was associated with younger age, lower education, concurrent Trichomonas vaginalis, bacterial vaginosis, and incident syphilis infection. Signs and symptoms were rare and not associated with either infection. CT was more prevalent, nearly 11%, compared to NG, 6.8%. The higher prevalence of CT could explain the lack of association with other STIs. The associations observed with NG could be the result of high-risk sexual networks or lack of protective immunity. Risk factors for CT and NG are distinct and may differ geographically, which should be considered when developing diagnostic tools or guiding presumptive treatment in specific populations.